Use of organic acids for reduction of microorganisms in shredded cabbage (Brassica oleracea) and carrot (Daucus carota) - Ruiz-Lobo, Dayana (2024)
Introduction. Alternative disinfection processes for fresh and minimally processed vegetables have been studied recently. Methods such as the use of organic acids can reduce microbial loads in foods. Objective. To evaluate the use of citric and lactic acids at different concentrations in reducing Escherichia coli and Listeria monocytogenes in shredded cabbage and carrot. Materials and methods. The study was conducted in San José, Costa Rica, between September and November 2023. Carrots and cabbages were shredded, inoculated with E. coli and L. monocytogenes, and then disinfected using lactic or citric acid at concentrations of 5, 10 y 20 g l-1 for 5 min. After disinfection, logarithmic reductions were determined, and orthogonal contrast and Bonferroni test were applied to evaluate the effect of the acids in comparison to the water control, the differences in the reduction between acids, and effect of the acid concentration. Results. In both carrot and cabbage, logarithmic reductions of E. coli between 2 and 5 log CFU/g were determined. Greater reductions were generally found at 20 g l-1 compared to 5 g l-1, and for lactic acid compared to citric acid. For L. monocytogenes in carrots, no reduction could be determined, however, in cabbage, reductions between 1,2 and 2,4 log CFU/g were determined, with higher reductions at 20 g l-1 compared to 5 g l-1 and for lactic acid compared to citric acid. Conclusions. Under studied concentration and time conditions, lactic and citric acids can be used in disinfection processes for shredded cabbage and carrot, achieving reductions of at least 2 log CFU/g.